1973
DOI: 10.1177/000348947308200224
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Facial Palsy and Pregnancy

Abstract: Idiopathic eripheral facial paralysis is a common clinical condition, but the etiology and preferred mole of treatment are still undecided. The currently popular etiological theory centers around disturbances of microvascular circulation. The literature contains conflicting statements on the incidence of this condition in pregnancy. Six cases are reported, one bilateral, in all of which the paralysis develo ed within six weeks of delivery. The incidence of facial paralysis was not significantly ifferent in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although Peitersen 3 suggested a less-favorable prognosis in pregnant women, no supportive data were outlined in his study. Other studies 5,6,12,[17][18][19] that report on recovery in pregnant females, although supportive of Peitersen's conclusions, are largely anecdotal, do not consider the severity of the paralysis at onset, and do not objectively grade recovery.…”
Section: Discussionmentioning
confidence: 95%
“…Although Peitersen 3 suggested a less-favorable prognosis in pregnant women, no supportive data were outlined in his study. Other studies 5,6,12,[17][18][19] that report on recovery in pregnant females, although supportive of Peitersen's conclusions, are largely anecdotal, do not consider the severity of the paralysis at onset, and do not objectively grade recovery.…”
Section: Discussionmentioning
confidence: 95%
“…Population-based incidence rates of Bell's palsy have been reported from areas within Europe [16,17,45,46], the United States [21,26,47], the Near East [20,25], South America [24] and Japan [27,28], While the number of population-based studies is limited, these rates are reasonably consistent and demon strate that the annual incidence of Bell's palsy in these populations appears to vary between 13 and 34 per 100,000 [47]. In addition to true differences between these populations, varying methods of case referral, ascertain ment, and diagnosis may account for the small differences noted between studies.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although none of the authors felt that their reports showed a statistically valid association, they hoped that their articles would point out the need for further study in this area. Since that time, several unsuccessful attempts have been made to establish or refute a definite relationship between idiopathic facial paralysis (Bell's palsy) and pregnancy.2.…”
mentioning
confidence: 96%